Impact of spatial configuration to spatial quality: Venice and Istanbul - Gümüş, İmran and Erdönmez, Ebru (Journal of Architecture and Urbanism, 2021)
The purpose of this study is to identify the relationship between spatial configuration and spatial quality, and how they affect each other. Spatial quality is a sophisticated concept and encompasses physical, social, economic, cultural and environmental components. Urban squares reflect these parameters and also play a decisive role in urban identity as areas of apparent urban culture and collective memory. Spatial configuration also determines the character of the squares as a result of morphological feature of cities. In the study, qualitative and quantitative methods are used together. Initially, the case study was conducted on two pier squares, San Marco Square (Venice) and Beşiktaş Square (Istanbul) according to fifty public space quality parameters. Secondly, morphological analysis was performed through space syntax method. It has been investigated whether there is a connection between spatial configuration and the factors determining the quality of space or not. As a result, it has been revealed that the spatial configuration is one of the determining factors being assessed the quality of the space, however, it does not provide sufficient data alone. The importance of this article is that it proposes an analytical approach that includes both quantitative and qualitative components of spatial quality.